Indignity of Labor: Role of Occupational Prestige in Unemployment - Baisakhi Marjit; Sugata Marjit; Kausik Gupta; Saibal Kar (Center for Economic Studies and ifo Institute (CESifo), 2022)
Occupational prestige or job status may induce people to remain unemployed even when jobs are available. Thus measured unemployment will always have a voluntary component. Accumulated wealth in a family tends to increase the opportunity cost of job search, more so in a world where job status is socially important. Thus prosperity and unemployment may go hand in hand independent of the standard income effect. The paper shows that measured unemployment always may have a voluntary component. In fact an increase in reservation wage increases voluntary unemployment. However, the impact on the level in involuntary unemployment of such an increase cannot be easily predicted.
Keywords: J24; J28; J33; 330; occupational prestige; reservation wage; ability to work; unemployment